If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.25x + 8.5 = x + 1 Reorder the terms: 8.5 + 0.25x = x + 1 Reorder the terms: 8.5 + 0.25x = 1 + x Solving 8.5 + 0.25x = 1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 8.5 + 0.25x + -1x = 1 + x + -1x Combine like terms: 0.25x + -1x = -0.75x 8.5 + -0.75x = 1 + x + -1x Combine like terms: x + -1x = 0 8.5 + -0.75x = 1 + 0 8.5 + -0.75x = 1 Add '-8.5' to each side of the equation. 8.5 + -8.5 + -0.75x = 1 + -8.5 Combine like terms: 8.5 + -8.5 = 0.0 0.0 + -0.75x = 1 + -8.5 -0.75x = 1 + -8.5 Combine like terms: 1 + -8.5 = -7.5 -0.75x = -7.5 Divide each side by '-0.75'. x = 10 Simplifying x = 10
| 16a=5a+33 | | 4x-12=6x-20 | | 4x-12=4x-20 | | 2x+x=1100 | | 3x-7=6x+2 | | -4(a-5b-c)= | | ln(x-3)+ln(x+1)=ln(x+7) | | 9.92x-6.13=5.96-7.28x | | 4x+2=3(x-2)+5 | | ln(x+5)=0 | | (16b-7)-5(3b+1)=-4 | | 7c-14d+c-d+7+5d= | | 2(3x+4)=6x+9 | | -16a+18a-a= | | 2x^2+4(x^2+3)-2=22 | | 27=3x | | 4+2x+7= | | 2*x+5=4*x-11 | | 10(2-x)+4x=-3(x+3) | | 2ab*2ab= | | 4x^2+2x-8=0 | | N+18=29 | | 6y+2(2y+2)=14 | | 35x-7y+56=0 | | 3(m+6)-2(m-3)=9 | | 2m-5(m+2)=-8-2m | | 8x+8=4x+12 | | -24x^3+9x^2+3x+1=0 | | 7y-8(4y-12)= | | 8x-(4x-8)=28 | | 4(x-3)+15=13 | | 2x^2+x=16 |